Nilotinib in Parkinson's disease: A systematic review and meta-analysis - Xie, Xiaolu; Yuan, Ping; Kou, Liqiu; Chen, Xiu; Li, Jun; Li, Yaling (Frontiers in Aging Neuroscience, 2022)
Background: Nilotinib, which inhibits cellular Abelson tyrosine kinase, may be an effective treatment for patients with Parkinson’s disease (PD). The purpose of this study is to evaluate the outcomes of different doses of nilotinib in patients with PD. Methods: We searched PubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Clinical Trials from inception to 7 March 2022 to identify all randomized controlled trials (RCTs) of nilotinib reporting outcomes of interest in patients with PD. Outcomes included tolerability, efficacy, safety, and CSF biomarker levels. Review manager 5.4 software was used to analyze all data. Results: Three RCTs with a total of 163 patients were included. No significant difference was found between 150mg nilotinib or 300mg nilotinib and placebo in terms of tolerability, adverse events, or HVA levels. 300mg nilotinib showed significantly higher Movement Disorder Society Unified Parkinson’s Disease Rating Scale Ⅲ (MDS-UPDRS Ⅲ) scores [SMD=0.52, 95%CI= (0.12, 0.92), P=0.01] and 3,4-dihydroxyphenylacetic acid (DOPAC) levels [SMD=0.52, 95%CI= (0.12, 0.92), P=0.01], and lower α-synuclein levels [SMD=-2.16, 95%CI= (-3.38, -1.84), P＜0.00001] compared with placebo. And compared with 150mg nilotinib, 300mg nilotinib showed significantly lower α-synuclein levels [SMD=-1.16, 95%CI= (-1.70, -0.61), P＜0.0001]. Conclusions: Although our study demonstrated favorable tolerability and safety of different doses of nilotinib, and improvement in part of CSF biomarker levels of 300mg nilotinib, the poor efficacy on motor outcomes indicated that nilotinib had no advantages in the clinic.